Variability in baseball throwing metrics during a structured long-toss program: Does one size fit all or should programs be individualized? - Leafblad, N. D.; Larson, D. R.; Fleisig, G. S.; Conte, S.; Fealy, S. A.; Dines, J. S.; D`Angelo, J.; Camp, J. L. (Sports Health: A Multidisciplinary Approach, 2019)
Background: The variability of throwing metrics, particularly elbow torque and ball velocity, during structured long-toss programs is unknown.